Clinical implication of quantitative flow ratio to predict clinical events after drug‐coated balloon angioplasty in patients with in‐stent restenosis. Issue 7 (19th May 2021) - Tang, Jiani; Hou, Hanjing; Chu, Jiapeng; Chen, Fei; Yao, Yian; Gao, Yanhua; Ye, Zi; Zhuang, Shaowei; Lai, Yan; Liu, Xuebo
Abstract: Background: The association between the quantitative flow ratio (QFR) and adverse events after drug‐coated balloon (DCB) angioplasty for in‐stent restenosis (ISR) lesions has not been investigated. Hypothesis: Post‐procedural QFR is related to adverse events in patients undergoing DCB angioplasty for ISR lesions. Methods: This retrospective study included data from patients undergoing DCB angioplasty for drug‐eluting stent (DES) ISR between January 2016 and February 2019. The QFR was measured at baseline and after DCB angioplasty. The endpoint was the vessel‐oriented composite endpoint (VOCE), defined as a composite of cardiac death, vessel‐related myocardial infarction, and ischemia‐driven target vessel revascularization. Results: Overall, 177 patients with 185 DES‐ISR lesions were included. During 1‐year follow‐up, 27 VOCEs occurred in 26 patients. The area under curve (AUC) of the post‐procedural QFR was statistically greater than that of the in‐stent percent diameter stenosis (0.77, 95% confidence interval [CI] 0.67–0.87 vs. 0.64, 95% CI 0.53–0.75; p = .032). Final QFR cutoff of 0.94 has the best predictive accuracy for VOCE. A QFR > 0.94 was associated with a lower risk of VOCE compared to a QFR ≤ 0.94 (log‐rank test, p < .0001). Survival analysis using the multivariable Cox model showed that a post‐procedural QFR ≤ 0.94 was an independent predictor of 1‐year VOCE (hazard ratio 6.53, 95% CI 2.70–15.8, p < .001). Conclusions: A lower QFR value was associated with worse clinical outcomes at 1 year after DCB angioplasty for DES‐ISR.